2017
DOI: 10.1016/j.ijheh.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound gel as an unrecognized source of exposure to phthalates and phenols among pregnant women undergoing routine scan

Abstract: Background Systemic absorption of phthalates and parabens has been demonstrated after dermal application of body lotion, and medical devices such as intravenous bags and tubing have been identified as a source of exposure to di(2-ethylhexyl) phthalate (DEHP). However, use of products during medical procedures such as aqueous gel applied during obstetrical ultrasound in pregnancy has not been investigated as a potential source of endocrine disrupting chemical (EDC) exposure. Human studies have associated EDCs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…69 Alterations were also seen for thyroid hormones 70 and semen parameters 71 in this same study. Messerlian et al 72 showed an increase in DEHP metabolites following dermal application of ultrasound gel during routine obstetrical scans at 20 weeks. Using results from NHANES (from 1999 to 2000 through 2013 and 2014) Romano et al 73 found an association between regular use of multivitamin/multimineral supplements and increased concentrations of MEP (11% higher) compared to nonusers; however, no association was seen with MBP.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…69 Alterations were also seen for thyroid hormones 70 and semen parameters 71 in this same study. Messerlian et al 72 showed an increase in DEHP metabolites following dermal application of ultrasound gel during routine obstetrical scans at 20 weeks. Using results from NHANES (from 1999 to 2000 through 2013 and 2014) Romano et al 73 found an association between regular use of multivitamin/multimineral supplements and increased concentrations of MEP (11% higher) compared to nonusers; however, no association was seen with MBP.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Both phthalates are then conjugated as glucuronides and to a small extent sulfates, and excreted via the urine (Phthalates 2008). Systemic absorption of phthalates has also been observed after the dermal application of personal care products (Janjua et al 2007, Witorsch andThomas 2010) including various antistretch mark creams and ultrasound gel products (Messerlian et al 2017). Some phthalate monoesters are products from more than one parent compound.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal douches have been implicated as a source of DEP among reproductive-aged women [31]. Other products used intravaginally or in the genital area, such as lubricant [26], ultrasound gel [32], and wipes [33], may also be sources of phthalate exposure. These exposures are widespread: in nationally representative surveys of U.S. women, 25% reported using vaginal lubricants in the past month [34], 62% reported ever using lubricant [34], and 18% reported douching in the past year [35].…”
Section: Introductionmentioning
confidence: 99%